ANALISIS PENGENDALIAN KUALITAS PRODUK SEPATU ADIDAS DENGAN METODE DMAIC DAN FMEA DI PT. PARKLAND WORLD INDONESIA-CIKANDE - Iik Dwi Aldi; Budiharjo Budiharjo; Asep Rahmatullah (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
Quality has become the most important force that results in organizational success. Defective products can have an impact on the company's image, customer satisfaction and even company revenue. Quality control measures by means of analysis and prevention need to be done reduce defects. The purpose of this study was to identify the number of defects in the Adidas Super Nova shoe product, the level of DPMO and the sigma value of the product With the six sigma method towards zero defect (zero failure rate). five stages in its application, namely Define, Measure, Analyze, Improve, and Control (DMAIC). The research results of PT. Parkland World Indonesi obtained types of defects in shoes, consisting of 3 types, namely bigreat defects, stitching defects, and gluing defects (gluing strength of the sole). From 20649 the number of shoes examined, the most dominant defect was bigreat defect (glue stain), of 556 or 42% so that the average sigma value was 3.50 sigma. The suggestion given to provide training to operators so that the operator's ability and understanding becomes better, supervise operators at work, carry out regular checks and maintenance on the machines used